The Effect of Career Training and Development on Job Satisfaction and its Implications for the Organizational Commitment of Regional Secretariat (SETDA) Employees of Jambi Provincial Government - Rahayu, Mieke; Rasid, Fahmi; Tannady, Hendy (International Review of Management and Marketing, 2019)
The purpose of this study was to determine The Effect of Career Training and Development both partially and simultaneously to the job satisfaction and the impact of Organizational Commitment. Using quantitative research methods, with a sample of 200 respondents from 665 populations. Data were analyzed using Structural Equation Modeling (SEM). Career development has a positive and significant effect on job satisfaction of the Regional Secretariat (SETDA) employees of the Jambi Provincial Government. Training has a positive and significant effect on the job satisfaction of the Regional Secretariat (SETDA) employees of the Jambi Provincial Government. Career development and training together have a positive and significant effect on job satisfaction of the Jambi Provincial Government Regional Secretariat (SETDA) employees with a coefficient of determination (R2) of 51%. Career development, job satisfaction as partial has a positive and significant effect on the commitment of the Regional Secretariat (SETDA) employee organization of the Jambi Provincial Government. Career development, training, and job satisfaction together have a positive and significant effect on the commitment of the Jambi Provincial Government Secretariat (SETDA) staff with a determination coefficient value (R2) of 79%. Keywords: Training, Career Development, Job Satisfaction and Organizational Commitment JEL Classifications: M12, M54, N75 https://doi.org/10.32479/irmm.7439